HJP bricks online ordering system. - Ziwewe, Nyasha Desire (Midlands State University, 2020)
This project focused on the development and implementation of an online ordering system for HJP Bricks private Limited. The main aim was to eliminate some manual processes in the ordering and selling of bricks at the organisation. The feasibility study was done with major focus on technical, economic, and operational feasibility. Costs involved in the development, maintenance and use of the system were estimated and weighed against the benefits. The results of the feasibility study were satisfactory since the constraints were within the organisation and the developer’s capacity. Risk analysis was also carried out and the results showed that the project was less risky. A project work-plan was developed following the favourable feasibility study and risk analysis. The project was planned where activity sequence and time allocation were determined. Using defined methodologies in data gathering, analysis of the system was carried out to determine if the organisation really need a new system. Information systems related problems were identified and also the weaknesses of the current system. The common problems affected data integrity, consistency, completeness and reliability of an information system at the organisation. The design of the solutions to the determined problems was done. All data-flows, processes, inputs, outputs and relations between entities in the new system were determined. The design includes system design, physical design, database design, architectural design and interface design. The high level design was converted into low level design and the design specifications were converted into working solutions. The solutions passed through different levels of testing from unit testing to integration testing. Different testing cases were determined and the system was tested to remove bugs. Verification and validation were done to determine if the right product was build and if it was built correctly. The system security mechanisms were formulated and some recommendations were given. For user training, a user manual was provided so that the use of the system will be easy.